MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA PEGAWAI PT. NOK PRECISION COMPONENT BATAM - Dedi Iswandi; Hazriyanto; Hazriyanto Hazriyanto (Journal of Innovation Research and Knowledge, 2026)
This research aims to determine the effect of intrinsic and extrinsic motivation on employee performance at PT. Nok Precision Component Batam. Intrinsic motivation includes internal drives such as the desire to achieve, personal satisfaction, and a sense of responsibility, while extrinsic motivation involves external factors such as salary, rewards, promotions, and a supportive work environment. Employee performance is assessed based on quantity, quality, punctuality, and teamwork. The research method used is quantitative with a survey approach. The sample consisted of 54 employees of PT. Nok Precision Component Batam, selected using simple random sampling. The research instrument was tested for validity and reliability. Data analysis was conducted with the assistance of SEM Smart PLS version 3.0. The results show that intrinsic motivation has a positive but not significant effect on employee performance, whereas extrinsic motivation has a positive, significant, and more dominant effect on employee performance. The coefficient of determination (R Square) value of 0.623 indicates that 62.3% of the variance in employee performance can be explained by the two motivation variables. Therefore, the company needs to prioritize the development of extrinsic motivation aspects, such as compensation and work environment, while still maintaining internal motivation to optimally enhance employee performance.